2019
DOI: 10.1590/s0102-865020190060000004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TLR4 in the protective effect of intra-articular administration of curcumin on rat experimental osteoarthritis

Abstract: and Technology, China. Design of the study, manuscript writing, critical revision, supervised all phases of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…A recent study conducted by Yan et al [168] suggested that the aforementioned beneficial role of curcumin administration in OA may be related to the inhibition of TLR-4 signal. Indeed, TLR-4 plays an important role in the pathogenesis of OA [169]. Several damage-associated molecular patterns (DAMPs) generated from cartilage damage can activate TLR-4 [169].…”
Section: Cur and Tlr-4 In Rheumatic Diseases Inflammatory Arthritic Dmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study conducted by Yan et al [168] suggested that the aforementioned beneficial role of curcumin administration in OA may be related to the inhibition of TLR-4 signal. Indeed, TLR-4 plays an important role in the pathogenesis of OA [169]. Several damage-associated molecular patterns (DAMPs) generated from cartilage damage can activate TLR-4 [169].…”
Section: Cur and Tlr-4 In Rheumatic Diseases Inflammatory Arthritic Dmentioning
confidence: 99%
“…Indeed, TLR-4 plays an important role in the pathogenesis of OA [169]. Several damage-associated molecular patterns (DAMPs) generated from cartilage damage can activate TLR-4 [169]. Moreover, the expression of TLR-4 in joint tissues increases with increasing severity of OA; this leads to inflammatory and catabolic responses by chondrocytes, represented by enhanced expression of inflammatory cytokines such as IL-1, IL-6, TNFα, and matrix metalloproteinase (MMP), release of nitric oxide (NO), and prostaglandin E2 (PGE2) synthesis, which are mediated by NF-κB [168][169][170].…”
Section: Cur and Tlr-4 In Rheumatic Diseases Inflammatory Arthritic Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin is widespread in many Asian cuisines as well as in Ayurvedic medicine [60]. Besides that, the antioxidant and anti-inflammatory properties of curcumin are well known [61], dealing with various pathologies such arthritis and osteoarthritis [62][63][64][65][66][67], obesity and diabetes [68,69]. In addition to its very low bioavailability, the real mechanism of action of curcumin is still uncertain.…”
Section: Nutritional Supplementsmentioning
confidence: 99%
“…In ammation contributes to chondrocyte apoptosis, extracellular matrix disruption, and cartilage degeneration through the pro-in ammatory cytokines IL1β, IL6, and TNF-α [58][59][60][61][62][63][64]. Curcumin has been suggested to suppress in ammation and prevent cartilage destruction by reducing the activation of the NF-κB pathway and proin ammatory cytokine expression [25,[65][66][67].…”
Section: Anti-in Ammatory Effect and Articular Cartilage Ameliorated mentioning
confidence: 99%